Associations between diet quality and knee joint structures, symptoms and systemic abnormalities in people with symptomatic knee osteoarthritis. Issue 5 (May 2021) - Ruan, Guangfeng; Yang, Chengliang; Meng, Tao; Zheng, Shuang; Zhang, Yan; Zhu, Jimin; Cen, Han; Wang, Yuanyuan; Zhu, Zhaohua; Han, Weiyu; Tang, Yujin; Liu, Jia; et al.
Summary: Background & aims: The evidence of benefiting from a high-quality diet for knee osteoarthritis (OA) joint structures, symptoms, and systemic abnormalities is limited. Clarifying the relationship between diet quality and knee OA could provide useful information for knee OA management. To investigate the associations between diet quality and knee joint structures, symptoms, lower limb muscle strength, depressive symptoms, and quality of life in people with knee OA. Methods: This study was a post-hoc, exploratory analysis using data from a randomized controlled trial in symptomatic knee OA participants with a follow-up time of 24 months. In brief, eligible participants of the original study were aged 50–79 years, had symptomatic knee OA, and had a pain of 20–80 mm on a 100-mm visual analog scale. After excluding the patients without information on diet quality, 392 participants were included in this post-hoc analysis. Diet quality was assessed at baseline using the Australian Recommended Food Score (ARFS) which includes subscores of vegetable, fruit, grain, dairy products, fat, and alcohol. Knee joint structures (including cartilage volume, cartilage defect, bone marrow lesions, and effusion-synovitis volume assessed by magnetic resonance imaging), OA symptoms, lower limb muscle strength, depressive symptoms, and quality of life were assessed at baseline and follow up. Mixed-effects models were used to assess the associations of diet quality with those outcomes. Results: Diet quality mainly reflect diet variety within the core food was not associated with knee structures and OA symptoms, but was associated with greater lower limb muscle strength (β = 0.66, P = 0.001), lower depressive symptom (β = -0.08, P = 0.001), and better quality of life (β = -0.06, P = 0.002). In further analyses of food group-based sub-scores, only the vegetable sub-score had the similar associations with lower limb muscle strength (β = 1.03, P = 0.004), depressive symptom (β = -0.17, P < 0.001), and quality of life (β = -0.14, P < 0.001). Conclusions: Higher diet quality, mainly vegetable diet quality, is associated with greater lower limb muscle strength, less depressive symptoms, and higher quality of life in knee OA patients, suggesting higher diet quality may have protective effects on knee OA.